Combined calcium looping and chemical looping combustion for post‐combustion carbon dioxide capture: process simulation and sensitivity analysis - Duhoux, Benoit; Mehrani, Poupak; Lu, Dennis Y.; Symonds, Robert T.; Anthony, Edward J.; Macchi, Arturo (Wiley, 2016)
In this work, a combined calcium looping and chemical looping combustion (CaL--CLC) technology is simulated at thermodynamic equilibrium conditions and the results in terms of efficiency, power production, and solids circulation rates are compared with the case of using CaL alone. In addition, a new solids looping configuration in the CaL--CLC process is proposed with the purpose of mitigating the loss of calcium oxide conversion after high cycle numbers. Simulations show an improved process efficiency of the CaL--CLC method compared with CaL alone (34.2 vs. 31.2 % higher heat value) and an increased power output (136 vs. 110 MWe additional power) due to the higher energy requirement to preheat the reactants. A sensitivity analysis of the process operating parameters highlights the particular importance of the temperature difference between reactors, which has a strong impact on the required mass of solids circulating in the loops. Finally, partial carbon dioxide capture scenarios are considered and indicate that lower capture levels are suitable to match regulation targets.
Keywords: calcium; carbon storage; chemical looping; combustion; process simulation